Babymouse. [1], Reina del universo - Holm, Jennifer L.; Holm, Matthew (Barcelona : SerreS, 2007)
An imaginative mouse dreams of being queen of the world, but will settle for an invitation to the most popular girl's slumber party.
3-6
Text in Spanish.
Translation of: Baby Mouse 1: Queen of the world!
Keywords: Popularity -- Comic books, strips, etc. -- Juvenile fiction; Imagination -- Comic books, strips, etc. -- Juvenile fiction; Friendship -- Comic books, strips, etc. -- Juvenile fiction; Mice -- Comic books, strips, etc. -- Juvenile fiction; Animals -- Comic books, strips, etc. -- Juvenile fiction; Popularity -- Fiction; Imagination -- Fiction; Spanish language materials; Friendship -- Fiction; Mice -- Fiction; Animals -- Fiction; Cartoons and comics; Popularity -- Comic books, strips, etc. -- Fiction; Imagination -- Comic books, strips, etc. -- Fiction; Spanish language; Friendship -- Comic books, strips, etc. -- Fiction; Mice -- Comic books, strips, etc. -- Fiction; Animals -- Comic books, strips, etc. -- Fiction; Comic books, strips, etc; Graphic novels; Graphic novels